Comprehensive genome profiling by next generation sequencing of circulating tumor DNA in solid tumors: a single academic institution experience. (May 2022) - Caputo, Vincenza; De Falco, Vincenzo; Ventriglia, Anna; Famiglietti, Vincenzo; Martinelli, Erika; Morgillo, Floriana; Martini, Giulia; Corte, Carminia Maria Della; Ciardiello, Davide; Poliero, Luca; De Vita, Ferdinando; Orditura, Michele; et al.
Background: Recently, new evidence of the next-generation sequencing (NGS) liquid biopsy utility in clinical practice has been developed. This assay is emerging as a new promising tool to use as a noninvasive biomarker for cancer mutation profiling. Additional data supporting the clinical validity of cell free DNA (cfDNA) based testing is necessary to inform optimal use of these assays in the clinic. Materials and methods: A total of 398 cancer patients were analyzed by FoundationOne Liquid Analysis (F1LA), a genomic profiling assay and by standard NGS diagnostic ThermoFisher platform. The association between diagnostic technique was evaluated using a Poisson regression model. FoundationOne Liquid (F1L) and FoundationOne Liquid CDx (F1LCDx) detect 70 and 324 cancer-related genes alterations, respectively, including genomic signatures tumor fraction, blood tumor mutational burden (only for the 324 genes version), and microsatellite instability high status. Both assays used a single DNA extraction method to obtain cfDNA. The real-life clinical impact and feasibility of F1L and F1LCDx were evaluated across different solid tumors in our department. Results: Between 1 January 2019 and 28 February 2021, 398 samples of different tumor types from 398 patients were analyzed (overall success rate: 92%, in FoundationOne Liquid CDx Analysis success rate: 97%). Most frequent molecular alterations were TP53 (74), APC (40), DNMT3A (39), KRAS (23). The comprehensive clinical impact of F1LA compared with standard diagnostic was 64.7% versus 22.1% [risk ratio (RR) = 2.94; p  < 0.001] and the potential clinical impact was 58.6% versus 11.0% (RR = 5.32; p  < 0.001), respectively. Furthermore, some clinical cases were selected, in which F1LA detected actionable alterations offering an unexpected therapeutic choice. Conclusions: Although additional studies are needed to better select patients and setting, NGS F1LA is a useful, noninvasive, and repeatable assay to guide therapeutic choice in oncology. It provides a snapshot of cancer heterogeneity profile that could be incorporated in routinely clinical practice.